The Effect of Services and Prices On Customer Satisfaction - Asfar, Andi Hasryningsih; Suripto, Puji (Bina Bangsa International Journal of Business and Management, 2021)
The orientation of the marketing world has changed from profit orientation to satisfaction orientation. Many companies implement strategies to improve service quality, increase customer satisfaction, and win the competition to increase profits. The researcher tries to prove that there is a positive and significant influence on the quality of service and that it can increase customer satisfaction and increase profits. This research was conducted at PT. Anugrah Argon Medica Branch Serang Banten, from the total population of 200 active customers taken samples from Slovin formula as many as 67 respondents. This researcher uses associative research methods with a quantitative correlational approach. Associative research is a research method. Based on the results of hypothesis testing that has been carried out, the t-test variable Service Quality (X1) 1.040 <1.997 and significance level of 0.302> 0.005, it turns out that service quality has no significant effect on customer satisfaction. From the results of the variable t-test Price (X2) 5,284> 1,996 and the significance level of 0,000 <0.05, it turns out the price has a positive and significant effect on Customer Satisfaction, the results of the F test results obtained 23,103> 3.14 and the significance level of 0,000 <0.05 turned out to be Service Quality, and Simultaneous prices have a positive and significant influence on customer satisfaction. From the results obtained, the value of R 0.648 while Adjusted R Square has amounted to 0.419 so that it can be concluded that the contribution of service quality and price to the dependent variable customer satisfaction simultaneously is 41.90%